Analisis Putusan Pengadilan Nomor 1815/K/Pdt/2021/PN.SBY Tentang Kelalaian Tenaga Medis Yang Mengakibatkan Cacat Bagi Pasien - Berliana, Putri Rizky; H. Arba (Private Law, 2024)
The aim of this research is to find out how to resolve disputes that occur when a doctor makes a mistake, causing disability for the patient, and the form of responsibility that the doctor must take when it is proven that he was wrong in carrying out treatment on his patient. The type of research used in this research is normative, this research focuses on statutory regulations and literature studies, so that primary legal materials become the main legal materials while secondary materials become supporting legal materials. The results of the research are dispute resolution regarding errors made by doctors which result in disability for their patients through litigation or court. The patient asks for justice for himself through the demands he submits. The form of responsibility of a doctor who is proven to have made a mistake in treating a patient is in the form of compensation and a fine that must be paid by the doctor, as well as the doctor admitting that he made a mistake during the first operation he performed on the victim's eye and writing a letter of apology.